An Estimation of the Effect of Women’s Employment on the Prevalence of Intimate Partner Violence in Mexico - Canedo, Ana P. (Journal of interpersonal violence, 2021)
Female labor force participation is important for women, children, and societies, but also may have unintended impacts including an increased risk of intimate partner violence (IPV). IPV is a global health, human rights, and development problem with far-reaching economic and societal consequences. Mexico has a very high prevalence of IPV: 43.9% of Mexican women have reported experiencing IPV at the hands of their current partner. The literature on women’s economic participation reveals mixed evidence on whether women’s employment is associated with higher levels of IPV or whether it is protective against IPV. As the effect of women’s work operates differently across contexts, we aim to estimate the effect of women’s employment on their risk of experiencing IPV in rural and urban Mexico. Utilizing the nationally representative 2016 Mexican National Survey on the Dynamics of Household Relationships (ENDIREH), we employ propensity score matching (PSM) to address the potential selection bias between women who are employed and/or receiving a cash transfer with women who are not. We additionally implement inverse probability weighted regression adjustment (IPWRA) to explore this relationship and compare the results with the PSM findings. Three different measures of women’s economic participation are analyzed: whether they had engaged in any productive work outside of the home in the past year, whether they received conditional cash transfers through Mexico’s Prospera program, and whether they received Prospera and worked. Given the high levels of IPV in Mexico and the greater levels of economic participation borne of an increased number of women in the workforce, our results have important potential implications for targeting support to survivors of violence who receive cash transfers and undertake employment in both urban and rural areas.